Uncover your creativity (Santa Monica, Calif. : Salenger Educational Media, 1986)
How can you increase your creativity? How can you improve your ability to discover new ideas and solve problems? This video suggests 6 fundamental ways to uncover creative ideas.
Copy available in DVD format
Keywords: Creative thinking; Creative ability; Thought and thinking